What Makes Your Day? A Study of the Quality of Worklife of OR Nurses - Donald, Joan (Operating Room Nurses Association of Canada Journal, 1999)
In the movie Dirty Harry, Clint Eastwood takes aim at a threatening criminal and says: “Go ahead, Make My Day!” Murder was in his eyes and in the intent of the comment.